Hubungan Aktivitas Fisik dengan Tingkat Keparahan Sindrom Ovarium Polikistik (SOPK) Sesuai dengan Skor Ferriman-Gallwey di Kota Ambon Tahun 2025 - Arlen Resnawaldi; Angel Noventia Taribuka; Joel Apriyanto Fejacreyo Huka (Jurnal Biomedika dan Kesehatan, 2026)
Background Polycystic Ovary Syndrome (PCOS) is a complex hormonal disorder commonly found among women of reproductive age, characterized by hyperandrogenism, ovulatory dysfunction, and polycystic ovarian morphology. One of its primary clinical manifestations is hirsutism, which is assessed using the Ferriman–Gallwey Score. Physical activity plays an important role in managing insulin resistance and androgen levels; however, no specific data are available regarding the relationship between physical activity and the severity of PCOS in Ambon City. Therefore, it is necessary to investigate the relationship between physical activity and PCOS severity, as measured by the Ferriman–Gallwey Score, in Ambon City in 2025. Methods This study used an analytical observational design with a cross-sectional approach. The sample comprised 60 reproductive-aged women with PCOS, recruited through consecutive sampling. Physical activity was measured with the IPAQ and categorized as light, moderate, or vigorous. PCOS severity was assessed using the Ferriman–Gallwey Score. Data were analyzed using the Chi-square test. Results Most respondents were 19–30 years old (70%) and 23.3% worked as housewives. The most common level of physical activity was light (53.3%), and the majority of respondents had mild PCOS (60%). A pattern was observed in which vigorous physical activity was associated with more severe PCOS. Chi-square analysis showed a statistically significant association between physical activity and PCOS severity (p < 0.001). Conclusions Physical activity was significantly associated with PCOS severity, with low activity linked to mild PCOS and vigorous activity predominantly linked to severe cases.